Practice of Buying and Selling Used Motorcycles (Study at Muh Yamin Motor) - Muh. Nuryamin Yunus; Mubarak Dahlan (PT. Gudang Pustaka Cendekia, 2026)
This study examines the socio-cultural dynamics inherent in the used motorcycle trading practices at the Muh Yamin Motor showroom. Utilizing a qualitative approach rooted in economic anthropology, this research shifts the focus from mere financial transactions to the underlying social structures that govern the local market ecosystem. Data were gathered through participant observation, in-depth interviews with the owner, mechanics, brokers (makelar), and customers, alongside comprehensive document analysis. The findings reveal that the sales process at Muh Yamin Motor is heavily embedded in informal social networks, verbal agreements, and ritualistic haggling behaviors. Rather than relying on formal legal contracts, transaction security and business sustainability are maintained through the continuous construction of mutual trust (trust) and personal reputation within the community. Furthermore, the operational mechanisms demonstrate how economic rationality coexists with social solidarity, transforming buyers into long-term social partners. This study concludes that the local used motorcycle industry operates as a socially embedded system where cultural values actively shape, facilitate, and regulate economic activities. Consequently, this research provides empirical insights into how traditional communal ethics endure and sustain modern informal marketplace behaviors in Indonesia.